Fabrication of W–Y2O3–La2O3 composite by chemical process and spark plasma sintering. (15th March 2021) - Lee, Eui Seon; Lee, Gyuhwi; Lee, Young-In; Jeong, Young-Keun; Oh, Sung-Tag
ABSTRACT: The fabrication of W composite with homogeneous dispersion of Y2 O3 and La2 O3 nanoparticles was attempted with the combination process of ultrasonic spray pyrolysis, polymeric additive solution route and spark plasma sintering processes. The Y2 O3 dispersed W powders were prepared by ultrasonic spray pyrolysis using ammonium metatungstate hydrate and yttrium nitrate. The composite powders with homogeneously coated La2 O3 on their surfaces were synthesised by calcination of a precursor solution containing lanthanum nitrate and polyvinyl alcohol. Microstructural analysis revealed that composite powders can be successfully produced by the ultrasonic spray pyrolysis and polymeric additive solution route. The composite powder was consolidated by spark plasma sintering yielding a sound microstructure and high hardness. The fine grain size and increased density in composite were mainly attributed to the dispersion of oxide particles and to the enhanced sinterability by the formation of liquid-like phase. The increased hardness was discussed by the observed microstructural features.